Asian Megaloptera in the Upper Silesian Museum Collection, Poland, with description of a new species of Protohermes van der Weele (Corydalidae: Corydalinae) from Vietnam - Liu, Xingyue; Dobosz, Roland (Zootaxa, 2019)
A list of Asian species of Megaloptera deposited in the Upper Silesian Museum which includes 35 species of Corydalidae and four species of Sialidae. A new species of the dobsonfly genus Protohermes van der Weele, 1907, P. stangei sp. nov. from central Vietnam is described. Protohermes weelei Navás, 1925 and Protohermes yangi Liu, Hayashi & Yang, 2007 are newly recorded from Laos and Sialis longidens Klingsted, 1932 is newly recorded from North Korea.